2003
DOI: 10.1021/jp034546u
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Supercapacitor Electrodes Using Fluorinated Single-Walled Carbon Nanotubes

Abstract: We have fabricated electrodes for a supercapacitor using fluorinated single-walled carbon nanotubes (SWCNTs). Although the specific surface areas of the pristine and fluorinated SWCNTs are similar, the electrochemical reactions are different significantly from each other. The specific capacitance of the fluorinated SWCNTs is smaller than that of the pristine sample particularly at large discharge current density, which can be attributed to the micropores formed during fluorination. After heat treatment at 900 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
50
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 21 publications
3
50
0
1
Order By: Relevance
“…1(b)]. In practice, different addition patterns are likely to coexist, resulting in a global F=C ratio consistent with the experimentally observed maximum coverage below 250 C of 20% to 25% [7,14,17]. However, as fluorine surface coverage increases, the average binding energy per F atom drops; our calculations for C 4 F give a binding energy per F of 1.75 eV for the (8,8) nanotube.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…1(b)]. In practice, different addition patterns are likely to coexist, resulting in a global F=C ratio consistent with the experimentally observed maximum coverage below 250 C of 20% to 25% [7,14,17]. However, as fluorine surface coverage increases, the average binding energy per F atom drops; our calculations for C 4 F give a binding energy per F of 1.75 eV for the (8,8) nanotube.…”
supporting
confidence: 77%
“…Fluorinated nanotubes can be used as precursors for further functionalization [3,4] and are soluble in a variety of common solvents [3,5], aiding tube bundle separation and purification. Potential applications for fluorinated nanotubes include use as electrodes in lithium-ion batteries [6], supercapacitors [7], and lubricants [8][9][10].…”
mentioning
confidence: 99%
“…The high specific capacitance of CNTs could also be obtained with the incorporation of heteroatoms such as N [61,[78][79][80][81][82][83][84][85][86][87], B [86][87][88][89], P [86,90], and F [91]. The type of defect created by the heteroatom influences the kind of conduction generated ranging from n-type transport (N substitution doping) to p-type conduction (B substitution of boron in lattice) [92].…”
Section: Covalent Modification Of Carbon Nanotubes and Their Capacitamentioning
confidence: 99%
“…[ 59,60,[232][233][234] With the presence of mesoporesc oming from the central canal and/or tube entanglement, CNTsh ave excellent access to the electrolyte. [235] Our group demonstrated that most of the BET surface area of SWCNT electrodes synthesized by directcurrenta rc discharge contributes to the theoretically estimated specific capacitance.…”
mentioning
confidence: 99%